The impact of sleep deprivation on the occurrence of acute coronary syndrome depending on obesity status - Kim, Ja Young; Eujene Jung,; Lee, Seonah (Journal of the Pakistan Medical Association, 2024)
Objective: To determine how sleep insufficiency affects the occurrence of acute coronary syndrome in the presence of obesity. Method: The observational study was conducted in South Korea on the basis of data collected by a cohort study conducted from January 2001 to December 2020, and comprised adults of either gender aged 40-69 years. During the 20-year period, 9 follow-up surveys were conducted at two-year intervals. Those with sleep <7 hours were in the insufficient sleep group A, and those with >7 hours of sleep were in the sufficient sleep group B. The main exposure variable was sleeping insufficiency, and the dependent variable was the occurrence of acute coronary syndrome. The hazard ratio between sleep insufficiency and obesity was identified, and the risk with respect to obesity was worked out. Finally, the joint effect of sleep insufficiency and obesity on the occurrence of acute coronary syndrome was determined. Data was analysed using SAS 9.4. Results: Of the 3,698 subjects, 2,411(65.2%) were in group A; 1,234(51.2%) females and 1,177(48.8%) males with mean age 50.4+/-7.55 years, and 1,287(34.8%) subjects were in group B; 747(58%) males and 540(42%) females with mean age 50.4+/-7.41 years. There were 1,637(44.3%) obese subjects; in group A 1,097(45.5%) and in group B 540(42%). Overall, 127(3.4%) subjects developed acute coronary syndrome; in group A 85(3.5%) and in group B 42(3.3%). Incidence of acute coronary syndrome was no significantly associated with sleep sufficiency and obesity status (p>0.05). The risk of developing acute coronary syndrome was significantly higher in obese individuals having sleep insufficiency compared to non-obese individuals without sleep insufficiency (hazard ratio: 1.54, 95% confidence interval: 1.03-2.62). Conclusion: There was a significant combined effect of obesity and sleep insufficiency on the occurrence of acute coronary syndrome. Key Words: Acute coronary syndrome, Obesity, Sleep insufficiency.